Influencia De Las Importaciones Del Acero Inoxidable De China En La Siderúrgica Colombiana (2023)
The work seeks to analyze what has been the impact of imports from China in the Colombian steel company, during the period 2015 to 2019, and analyze if there were variations during the COVID19 pandemic, fulfilling the development of the objectives by doing qualitative research that allows the development of this.